Career Decision-Making among Rural Senior Secondary Students: The Role of Parental Encouragement across Three Indian States - , Poonam Yadav; , Asha Chawla Thakral; , Deepika Vig (Archives of Current Research International, 2025)
The study was conducted to examine the relationship between parental encouragement and career decision-making among 900 rural senior secondary students from socio-cultural zones across three Indian states namely Punjab, Haryana and Uttarakhand. To assess the various dimensions of parental encouragement at different levels, a self-structured parental encouragement questionnaire was used. The study explored parental encouragement among students across zones in Punjab, Haryana and Uttarakhand. A self-structured parental encouragement questionnaire was used to assess the extent of parental encouragement perceived by senior secondary students for career decision making. Equal proportion of boys and girls were randomly chosen for the data collection. Frequency, Percentages and Z-Test were the statistical tools used in the study to analyse the results. Findings of the study revealed that Punjab showed the highest levels of parental encouragement, particularly in Doaba zone. Haryana and Uttarakhand demonstrated moderate yet varied encouragement across different zones. Gender differences revealed that girls generally received more support, especially in decision-making and verbal encouragement, though some zones showed no notable gender differences, reflecting diverse patterns of parental encouragement.